VD_FINDINFO Jug / 2012 / 251 vom 8. Mai 2012 - VD Tribunal cantonal (2012)
VOIES DE FAIT, INJURE, CONSTATATION DES FAITS, CONTRAINTEDROIT PÉNAL | 126 al. 1 CP, 177 al. 1 CP, 177 al. 2 CP, 177 al. 3 CP, 181 CP, 49 al. 1 CP